2021
DOI: 10.3389/fncel.2021.644047
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering in silico the Role of Mutated NaV1.1 Sodium Channels in Enhancing Trigeminal Nociception in Familial Hemiplegic Migraine Type 3

Abstract: Familial hemiplegic migraine type 3 (FHM3) is caused by gain-of-function mutations in the SCN1A gene that encodes the α1 subunit of voltage-gated NaV1.1 sodium channels. The high level of expression of NaV1.1 channels in peripheral trigeminal neurons may lead to abnormal nociceptive signaling thus contributing to migraine pain. NaV1.1 dysfunction is relevant also for other neurological disorders, foremost epilepsy and stroke that are comorbid with migraine. Here we used computer modeling to test the functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 79 publications
(206 reference statements)
0
1
0
Order By: Relevance
“…It has been reported that anandamide (AEA) can activate the transient receptor potential vanilloid receptor (TRPV1) to trigger the release of CGRP and promote nociceptive signaling [ 72 ]. In the TGVS, many pain-related ion channels are located in the meningeal afferents and can be targeted by 2-AG and AEA [ 73 , 74 ]. Since the activity of most ion channels depends on membrane lipids such as phosphatidylinositol 4,5-bisphosphate (PIP2) and specific fatty acids [ 75 , 76 ], the endocannabinoid-metabolized lipid profile allows them to modulate mechanosensitive ion channels through noncanonical lipid signaling.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that anandamide (AEA) can activate the transient receptor potential vanilloid receptor (TRPV1) to trigger the release of CGRP and promote nociceptive signaling [ 72 ]. In the TGVS, many pain-related ion channels are located in the meningeal afferents and can be targeted by 2-AG and AEA [ 73 , 74 ]. Since the activity of most ion channels depends on membrane lipids such as phosphatidylinositol 4,5-bisphosphate (PIP2) and specific fatty acids [ 75 , 76 ], the endocannabinoid-metabolized lipid profile allows them to modulate mechanosensitive ion channels through noncanonical lipid signaling.…”
Section: Discussionmentioning
confidence: 99%
“…52 ). The dissociation of these phenotypes may have several explanations: The pain threshold may be higher in Dravet syndrome because of a deficiency of peripheral Scn1a /Nav1.1 channels maintaining sensory nerve excitation ( 53 ), whereas FHM3-linked Scn1a gain-of-function mutations might reduce this threshold ( 54 ) and intensify headache sensation. FHM may represent a rare form of migraine linked to high SD susceptibility involving motor-related cortical regions, and SD generated in epilepsy may accompany distinct focal functional impairment depending on the affected brain region ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“… 166 Additionally, the Nav1.1 channel with L263V missense mutation enhances spike activity induced by P2X3 and 5-HT3 receptors, increasing the excitability of peripheral trigeminal neurons and contributing to migraine pain . 167 …”
Section: Molecular Mechanisms Of Pain Modulationmentioning
confidence: 99%